Klitores Kaos e o grito das mulheres: o Punk/HC desemboca numa cena musical feminista em Belém do Pará - MONTEIRO, Keila Michelle Silva (Universidade Federal do Pará, 2023)
This research focuses on the punk/hc music scene, a subgenre of rock, in Belém do Pará, made up of women as a necessary musical practice in combating existing prejudices among people who perform or frequent environments of this genre, in which predominates , still, the male sex, because rock and its aspects, despite representing transgression and going against oppression and violence from the State and society, sometimes make female production invisible and its actors still practice machismo, misogyny, among other attitudes that offend women. In this ethnography, I approach the trajectory of punk/hc in Belém do Pará, emphasizing female/feminist musical production, making it necessary to value this production and emphasize the need to respect women in this scenario, because, according to Rosa and Nogueira, “poetry and music are born of the ruptures and the pain they transform. It is a creative process in the broadest sense where, by creating artistic paths and producing our own knowledge, we also reinvent ourselves as people” (2015, p. 27). I will analyze the trajectory, performance, aesthetics and musical compositions of the band Klitores Kaos, which works to claim rights and empower women, in a dialogue with Chada (2011), Béhague (1992, 1999), Blacking (1973) and Merriam (1964) to deal with socioeconomic factors present in the songs; O´Hara (2005) and Caiafa (1985) to address the context of the punk rock genre. In addition to the studied bibliography, I used media files and field research material before the pandemic. According to the analysis of the band's performance and aesthetics, its trajectory and mainly the musical analysis in this research, the data point to a production of protest, a 'cry' to combat femicide, sexism, misogyny and racism with women taking up spaces and the growing respect for the female gender in the punk/hc scene, which is often confused with the private lives of these women.